Ventilation in chronic heart failure: effects of physical training. Issue 11 (November 1992) - Davey, P; Meyer, T; Coats, A; Adamopoulos, S; Casadei, B; Conway, J; Sleight, P
Abstract : Objective —To assess the effects of exercise training on ventilatory function in chronic heart failure. Design —Observer blinded random allocation crossover training and detraining trial. Setting —Assessment in hospital based clinical laboratory; training home based. Patients —22 patients with chronic heart failure (New York Heart Association (NYHA) class II or III) recruited from a tertiary referral centre. All finished the study. Intervention —Bicycle ergometer exercise for 20 minutes a day, five days a week for eight weeks at 70%–80% of maximum heart rate. Main outcome measures —Exercise capacity on graded incremental exercise test, minute ventilation, oxygen consumption and carbon dioxide output. Results —Peak work load increased from 96 W to 112 W and peak oxygen consumption from 14·1 ml`/kg/min to 15·4 ml/kg/min (p < 0·01). At submaximal workloads carbon dioxide excretion (Vco 2 ) and minute ventilation (Vi) decreased significantly (p < 0·05) though oxygen consumption was unchanged. The relation between Vi and carbon dioxide excretion changed: the slope of the Vi to Vco 2 plot decreased from 38·6 to 35·3, indicating an improvement in overall ventilary efficiency. The instantaneous carbon dioxide ventilatory equivalent (Vi/Vco 2 ) decreased at submaximal workloads, and reached a lower mimimum value after training, indicating that optimum ventilatory performance improved. The exercise capacity of patients was related to the optimum ventilatory performance. It is suggested that this may in part be mediated through changes in skeletal muscles. Conclusion —Exercise training reduces the ventilatory abnormalities in chronic heart failure; thus some of these changes may be due to physical deconditioning.